Smelting process of cupola furnace
By pretreating the furnace charge and furnace body of the hedge furnace and coating the furnace material, combining oxygen-rich blower smelting and alternating feeding processes, as well as magnetization treatment of iron liquid, the problems of furnace lining cracks and temperature differences are solved, and the strength and toughness of the castings are significantly improved.
Patent Information
- Application Number
- CN202510129194.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-22
AI Technical Summary
In the existing cupola smelting process, the furnace lining is prone to cracks or peeling under thermal shock, resulting in a difference in the internal temperature of the iron and affecting the product quality of the castings.
The uniformity and strength of the furnace and furnace body are ensured through furnace material pretreatment and furnace body treatment, including sandblasting, crushing, screening and furnace material coating. The process of oxygen-rich blower smelting and alternating feeding is adopted to ensure the stable state of heat and materials in the furnace. Finally, the discharged iron liquid is magnetized to change its crystallization method and promote the formation of fine crystal nuclei.
Through these measures, the strength and toughness of the castings are significantly improved, temperature inhomogeneity is reduced, and the overall quality of the castings is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of smelting, in particular to a smelting process of a cupola. Background Art
[0002] Cupola smelting process is an important metal smelting method, which is mainly used for melting alloys in casting production.
[0003] In the prior art, for example, patent CN105734395A discloses a cupola smelting process, which includes the following steps: material preparation: including the components of coke, pig iron, ferroalloy, limestone and other materials, the maximum size of the metal material shall not exceed one-third of the furnace diameter near the charging port, and scrap steel and recycled iron with severe rust must be treated before being put into the furnace; various types of furnace materials shall be classified and stacked, and shall not be mixed. Untreated shells, waste guns and other dangerous objects shall not be mixed in, and harmful debris such as rubber and plastic shall be prevented from being put into the furnace; recipe: repairing the furnace and baking the furnace; after baking the furnace, adding firewood, igniting the fire, and opening the tuyere cover for natural ventilation; loading; smelting with air.
[0004] In the above patent, the smelting process is simple, which eliminates many repetitive processes and improves work efficiency. However, during the smelting process, the furnace lining is prone to cracking or peeling due to thermal shock, causing the heat in the furnace to dissipate through the cracks, resulting in temperature differences inside the molten iron, making it impossible to evenly maintain the molten iron within the appropriate smelting temperature range, thereby reducing the product quality of subsequent castings.
[0005] Based on this, the present invention provides a smelting process for a cupola. Summary of the invention
[0006] The purpose of the present invention is to provide a cupola smelting process. The casting prepared by the present invention has higher strength and toughness.
[0007] To achieve the above object, the present invention provides the following technical solution: a smelting process of a cupola furnace, comprising the following steps:
[0008] S1: Charge pretreatment: Pig iron, scrap steel and recycled materials are selected for charge pretreatment, which are sandblasted, crushed and sieved before adding adsorbent for mixing;
[0009] S2: furnace body treatment, using furnace repair materials to evenly coat the inner wall of the furnace body to complete the furnace body treatment;
[0010] S3: charging process, charging in the order of bottom coke, furnace charge, layer coke and limestone, and completing the charging process;
[0011] S4: Smelting treatment, burning the bottom coke and the layer coke through oxygen-enriched blast smelting to complete the smelting treatment of the charge;
[0012] S5: pouring process: the smelted charge is discharged through the iron outlet of the furnace body, and is magnetized and poured into the mold.
[0013] Furthermore, the charge pretreatment method is as follows: the charge is selected from pig iron, scrap steel and recycled charge, the mass ratio of pig iron, scrap steel and recycled charge is 5:3:2, and then quartz sand is sent into the sandblasting machine, the charge is placed within the working range of the sandblasting machine, the pressure of the sandblasting machine is set to 0.6-0.8MPa, the distance between the sandblasting gun and the drill bit is 150-200mm, and the sandblasting gun maintains a displacement speed of 0.6-0.8mm. After the sandblasting is completed, the charge is crushed by a jaw crusher, and the jaw crusher is set to 200-300r / min for 10-20min. The crushed charge is sieved with a 2-5 mesh sieve, and then the sieved charge and adsorbent are added to the mixer for mixing, the mass ratio of the charge box and the adsorbent is 1:0.005, and the pretreatment of the charge is completed.
[0014] Furthermore, the adsorbent is made by mixing calcium oxide and magnesium oxide, the mass ratio of calcium oxide to magnesium oxide is 7:3, the purity of the calcium oxide is 95%, and the purity of the magnesium oxide is 92%.
[0015] Furthermore, the repair material in the furnace body treatment in S2 is prepared by the following method: memory alloy powder and carbon fiber are pretreated and then added into a mixer together with silicon carbide powder, aluminate cement and graphite powder for mixing.
[0016] Furthermore, the particle size of the silicon carbide powder is 20-60 μm, the particle size of the aluminate cement is 30-70 μm, the particle size of the graphite powder is 10-40 μm, and the shape memory alloy powder is nickel-titanium shape memory alloy powder.
[0017] Furthermore, the memory alloy powder pretreatment method is as follows: after screening the memory alloy powder with a 200-mesh screen, the memory alloy powder is added to a glass container, and a hydrofluoric acid solution is added for soaking. During the soaking process, a magnetic stirrer is used for continuous stirring at a stirring speed of 1000-1500r / min. After the soaking is completed, it is washed with clean water 6-8 times, and then placed in a dryer for drying. The drying temperature is 60-80°C and the drying time is 1-2h to complete the pretreatment of the memory alloy powder. The mass ratio of the memory alloy powder to the hydrofluoric acid solution is 1:0.7, and the concentration of the hydrofluoric acid solution is 4%.
[0018] Furthermore, the carbon fiber pretreatment method is to put the carbon fiber into an ultrasonic cleaning machine, treat it at 160 to 200 kHz for 16 to 20 minutes, take it out and drain it, thereby completing the pretreatment of the carbon fiber.
[0019] Furthermore, the charging method is to add bottom coke at the bottom of the furnace body with a thickness of 10-20 cm, add the charge to the bottom coke with a thickness of 15-25 cm, then add layer coke with a thickness of 3-5 cm, and finally add limestone with a thickness of 10-30 mm, and then repeat the above charging sequence to achieve alternating charging. Both the bottom coke and the layer coke are metallurgical coke with a carbon content of 85%, and the charging process is completed.
[0020] Furthermore, the smelting treatment method is to use a blower to carry out oxygen-enriched blast smelting, the oxygen content is 25%-30%, and the blast intensity is 100-200m 3 / (㎡·h), set the melting temperature to 1500-1600℃, the melting time to 20-30min, and complete the melting process.
[0021] Furthermore, the casting treatment method is that after the internal furnace charge is smelted, the molten iron is discharged through the furnace body discharge port. During the discharge process, a magnetic field generator is used for magnetization treatment, and the magnetic field strength is 0.05-0.08T. It is then poured into a mold and taken out after cooling to obtain a casting.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. In the present invention, in the treatment of the furnace body, by coating the furnace repair material inside the furnace body, when the temperature changes sharply during the smelting process, the memory alloy powder absorbs and releases heat through phase change by virtue of the shape memory effect to relieve thermal stress, and the carbon fiber utilizes the high thermal conductivity to evenly distribute the heat to prevent the furnace repair material from cracking due to thermal stress. The carbon fiber changes the heat transfer of the molten iron in the furnace by virtue of the high thermal conductivity, so that the temperature gradient is more reasonable and uniform when the casting solidifies, and promotes the formation of uniform and fine solidification structure. The memory alloy powder plays a positive role in optimizing the solidification structure of the casting by maintaining a stable smelting temperature, so that the fine and uniform solidification structure formed by the casting can improve the strength and toughness.
[0024] 2. The present invention realizes alternating charging by repeating the charging sequence, so that the temperature distribution in the furnace and the melting process of the charge can be made more uniform. Each layer of charge and coke layer cooperate with each other during the melting and combustion process, ensuring that the heat and materials inside the entire furnace body are in a relatively stable state, making the composition and temperature of the smelted iron liquid more uniform, which is beneficial to the subsequent pouring process and improves the quality of the castings.
[0025] 3. The present invention magnetizes the discharged molten iron, which causes the iron atoms to be affected by the Lorentz force during crystallization, thereby changing the diffusion and arrangement of the atoms, inhibiting the growth of grains, and prompting the molten iron to form more crystal nuclei, thereby refining the grains, increasing the grain boundary area, and hindering dislocation movement, thereby improving the strength, hardness and toughness of the casting. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below.
[0028] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.
[0029] Embodiment 1:
[0030] A cupola smelting process comprises the following steps:
[0031] S1: Charge pretreatment: Pig iron, scrap steel and recycled materials are selected for charge pretreatment, which are sandblasted, crushed and sieved, and then adsorbent is added to mix;
[0032] S2: furnace body treatment, using furnace repair materials to evenly coat the inner wall of the furnace body to complete the furnace body treatment;
[0033] S3: charging process, charging in the order of bottom coke, furnace charge, layer coke and limestone, and completing the charging process;
[0034] S4: Smelting treatment, burning the bottom coke and the layer coke through oxygen-enriched blast smelting to complete the smelting treatment of the charge;
[0035] S5: pouring process: the smelted charge is discharged through the iron outlet of the furnace body, and is magnetized and poured into the mold.
[0036] The charge pretreatment method is as follows: the charge includes pig iron, scrap steel and recycled charge, the mass ratio of pig iron, scrap steel and recycled charge is 5:3:2, and then quartz sand is sent into the sandblasting machine, and the charge is placed within the working range of the sandblasting machine. The pressure of the sandblasting machine is set to 0.6MPa, the distance between the sandblasting gun and the drill bit is 150mm, and the sandblasting gun maintains a displacement speed of 0.6mm. After the sandblasting is completed, the charge is crushed by a jaw crusher, and the jaw crusher is set at 200r / min for 10min. The crushed charge is sieved with a 2-mesh sieve, and then the sieved charge and adsorbent are added to the mixer for mixing. The mass ratio of the charge box and the adsorbent is 1:0.005, and the pretreatment of the charge is completed.
[0037] The adsorbent is made of a mixture of calcium oxide and magnesium oxide, the mass ratio of calcium oxide to magnesium oxide is 7:3, the purity of calcium oxide is 95%, and the purity of magnesium oxide is 92%.
[0038] The repair material in the furnace body treatment in S2 is prepared by the following method: memory alloy powder and carbon fiber are pretreated, and then added into a mixer together with silicon carbide powder, aluminate cement and graphite powder for mixing.
[0039] The particle size of silicon carbide powder is 20 μm, the particle size of aluminate cement is 30 μm, the particle size of graphite powder is 10 μm, and the shape memory alloy powder is nickel-titanium shape memory alloy powder.
[0040] The pretreatment method of the memory alloy powder is as follows: after screening the memory alloy powder with a 200-mesh screen, the memory alloy powder is added into a glass container, and a hydrofluoric acid solution is added for soaking. During the soaking process, a magnetic stirrer is used for continuous stirring at a stirring speed of 1000r / min. After the soaking is completed, the powder is washed with clean water for 6 times, and then placed in a dryer for drying at a drying temperature of 60°C and a drying time of 1h to complete the pretreatment of the memory alloy powder. The mass ratio of the memory alloy powder to the hydrofluoric acid solution is 1:0.7, and the concentration of the hydrofluoric acid solution is 4%.
[0041] The pretreatment method of the carbon fiber is to put the carbon fiber into an ultrasonic cleaning machine, treat it for 16 minutes under the condition of 160kHz, take it out and drain it, thereby completing the pretreatment of the carbon fiber.
[0042] The charging method is to add bottom coke at the bottom of the furnace body with a thickness of 10 cm, then add the charge to the bottom coke with a thickness of 15 cm, then add layer coke with a thickness of 3 cm, and finally add limestone with a thickness of 10 mm, and then repeat the above charging sequence to achieve alternating charging. Both the bottom coke and the layer coke are metallurgical coke with a carbon content of 85%, and the charging process is completed.
[0043] The smelting treatment method is to use a blower for oxygen-enriched blast smelting, with an oxygen content of 25%-30% and a blast intensity of 100m 3 / (㎡·h), set the melting temperature to 1500℃, the melting time to 20min, and complete the melting process.
[0044] The pouring treatment method is that after the internal charge is smelted, the molten iron is discharged through the discharge port of the furnace body. During the discharge process, a magnetic field generator is used for magnetization treatment with a magnetic field strength of 0.05, and then it is poured into a mold and taken out after cooling to obtain a casting.
[0045] Embodiment 2:
[0046] A cupola smelting process comprises the following steps:
[0047] S1: Charge pretreatment: Pig iron, scrap steel and recycled materials are selected for charge pretreatment, which are sandblasted, crushed and sieved, and then adsorbent is added to mix;
[0048] S2: furnace body treatment, using furnace repair materials to evenly coat the inner wall of the furnace body to complete the furnace body treatment;
[0049] S3: charging process, charging in the order of bottom coke, furnace charge, layer coke and limestone, and completing the charging process;
[0050] S4: Smelting treatment, burning the bottom coke and the layer coke through oxygen-enriched blast smelting to complete the smelting treatment of the charge;
[0051] S5: pouring process: the smelted charge is discharged through the iron outlet of the furnace body, and is magnetized and poured into the mold.
[0052] The charge pretreatment method is as follows: pig iron, scrap steel and recycled materials are selected as the charge, and the mass ratio of pig iron, scrap steel and recycled materials is 5:3:2. Then quartz sand is sent into the sandblasting machine, and the charge is placed within the working range of the sandblasting machine. The pressure of the sandblasting machine is set to 0.7MPa, the distance between the sandblasting gun and the drill bit is 175mm, and the sandblasting gun maintains a displacement speed of 0.7mm. After sandblasting, the charge is crushed by a jaw crusher, and the jaw crusher is set to 250r / min for 15min. The crushed charge is sieved with a 3.5-mesh sieve, and then the sieved charge and adsorbent are added to the mixer for mixing. The mass ratio of the charge box and the adsorbent is 1:0.005, and the pretreatment of the charge is completed.
[0053] The adsorbent is made of a mixture of calcium oxide and magnesium oxide, the mass ratio of calcium oxide to magnesium oxide is 7:3, the purity of calcium oxide is 95%, and the purity of magnesium oxide is 92%.
[0054] The repair material in the furnace body treatment in S2 is prepared by the following method: memory alloy powder and carbon fiber are pretreated, and then added into a mixer together with silicon carbide powder, aluminate cement and graphite powder for mixing.
[0055] The particle size of silicon carbide powder is 40 μm, the particle size of aluminate cement is 50 μm, the particle size of graphite powder is 25 μm, and the shape memory alloy powder is nickel-titanium shape memory alloy powder.
[0056] The pretreatment method of the memory alloy powder is as follows: after screening the memory alloy powder with a 200-mesh sieve, the memory alloy powder is added into a glass container, and a hydrofluoric acid solution is added for soaking. During the soaking process for 7.5 minutes, a magnetic stirrer is used for continuous stirring at a stirring speed of 1250r / min. After the soaking is completed, it is washed with clean water 7 times and then placed in a dryer for drying at a drying temperature of 70°C and a drying time of 1.5 hours to complete the pretreatment of the memory alloy powder. The mass ratio of the memory alloy powder to the hydrofluoric acid solution is 1:0.7, and the concentration of the hydrofluoric acid solution is 4%.
[0057] The pretreatment method of the carbon fiber is to put the carbon fiber into an ultrasonic cleaning machine, treat it for 18 minutes under the condition of 1180kHz, take it out and drain it, thereby completing the pretreatment of the carbon fiber.
[0058] The charging method is to add bottom coke at the bottom of the furnace body with a thickness of 10-20cm, then add the charge to the bottom coke with a thickness of 20cm, then add layer coke with a thickness of 4cm, and finally add limestone with a thickness of 20mm, and then repeat the above charging sequence to achieve alternating charging. Both the bottom coke and the layer coke are metallurgical coke with a carbon content of 85%, and the charging process is completed.
[0059] The smelting treatment method is to use a blower for oxygen-enriched blast smelting, with an oxygen content of 25%-30% and a blast intensity of 150m 3 / (㎡·h), set the melting temperature to 1550℃, the melting time to 25min, and complete the melting process.
[0060] The pouring treatment method is that after the internal charge is smelted, the molten iron is discharged through the discharge port of the furnace body. During the discharge process, a magnetic field generator is used for magnetization treatment with a magnetic field strength of 0.06T. Then it is poured into a mold and taken out after cooling to obtain a casting.
[0061] Embodiment three:
[0062] A cupola smelting process comprises the following steps:
[0063] S1: Charge pretreatment: Pig iron, scrap steel and recycled materials are selected for charge pretreatment, which are sandblasted, crushed and sieved before adding adsorbent for mixing;
[0064] S2: furnace body treatment, using furnace repair materials to evenly coat the inner wall of the furnace body to complete the furnace body treatment;
[0065] S3: charging process, charging in the order of bottom coke, furnace charge, layer coke and limestone, and completing the charging process;
[0066] S4: Smelting treatment, burning the bottom coke and the layer coke through oxygen-enriched blast smelting to complete the smelting treatment of the charge;
[0067] S5: pouring process: the smelted charge is discharged through the iron outlet of the furnace body, and is magnetized and poured into the mold.
[0068] The charge pretreatment method is as follows: the charge is selected from pig iron, scrap steel and recycled materials, the mass ratio of pig iron, scrap steel and recycled materials is 5:3:2, and then quartz sand is sent into the sandblasting machine, the charge is placed within the working range of the sandblasting machine, the pressure of the sandblasting machine is set to 0.8MPa, the distance between the sandblasting gun and the drill bit is 200mm, and the sandblasting gun maintains a displacement speed of 0.8mm. After the sandblasting is completed, the charge is crushed by a jaw crusher, and the jaw crusher is set at 300r / min for 20min. The crushed charge is sieved with a 5-mesh screen, and then the sieved charge and adsorbent are added to the mixer for mixing, the mass ratio of the charge box and the adsorbent is 1:0.005, and the pretreatment of the charge is completed.
[0069] The adsorbent is made of a mixture of calcium oxide and magnesium oxide, the mass ratio of calcium oxide to magnesium oxide is 7:3, the purity of calcium oxide is 95%, and the purity of magnesium oxide is 92%.
[0070] The repair material in the furnace body treatment in S2 is prepared by the following method: memory alloy powder and carbon fiber are pretreated, and then added into a mixer together with silicon carbide powder, aluminate cement and graphite powder for mixing.
[0071] The particle size of silicon carbide powder is 60 μm, the particle size of aluminate cement is 70 μm, the particle size of graphite powder is 40 μm, and the shape memory alloy powder is nickel-titanium shape memory alloy powder.
[0072] The pretreatment method of the memory alloy powder is as follows: after screening the memory alloy powder with a 200-mesh sieve, the memory alloy powder is added into a glass container, and a hydrofluoric acid solution is added for soaking. During the soaking process, a magnetic stirrer is used for continuous stirring at a stirring speed of 1500r / min. After the soaking is completed, it is washed with clean water 8 times, and then placed in a dryer for drying at a drying temperature of 80°C and a drying time of 2h to complete the pretreatment of the memory alloy powder. The mass ratio of the memory alloy powder to the hydrofluoric acid solution is 1:0.7, and the concentration of the hydrofluoric acid solution is 4%.
[0073] The pretreatment method of the carbon fiber is to put the carbon fiber into an ultrasonic cleaning machine, treat it at 200kHz for 20 minutes, take it out and drain it, thereby completing the pretreatment of the carbon fiber.
[0074] The charging method is to add bottom coke to the bottom of the furnace body with a thickness of 20 cm, then add the charge to the bottom coke with a thickness of 25 cm, then add layer coke with a thickness of 5 cm, and finally add limestone with a thickness of 30 mm, and then repeat the above charging sequence to achieve alternating charging. Both the bottom coke and the layer coke are metallurgical coke with a carbon content of 85%, and the charging process is completed.
[0075] The smelting treatment method is to use a blower for oxygen-enriched blast smelting, with an oxygen content of 30% and a blast intensity of 200m 3 / (㎡·h), set the melting temperature to 1600℃, the melting time to 30min, and complete the melting process.
[0076] The pouring treatment method is that after the internal charge is smelted, the molten iron is discharged through the discharge port of the furnace body. During the discharge process, a magnetic field generator is used for magnetization treatment with a magnetic field strength of 0.08T. Then it is poured into a mold and taken out after cooling to obtain a casting.
[0077] Comparative Example 1: The difference between this comparative example and Experiment 1 is that the repair material is not improved in this comparative example.
[0078] Comparative Example 2: The difference between this comparative example and Experiment 1 is that in this comparative example, the charge is not alternately added.
[0079] Comparative Example 3: The difference between this comparative example and Experiment 1 is that in this comparative example, no magnetization treatment is performed when the molten iron is discharged.
[0080] Performance test: Mechanical tests were performed on the castings made in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3.
[0081] The test data obtained are recorded in the following mechanical test table.
[0082] Mechanical test table:
[0083]
[0084] By comparing and analyzing the relevant data in the table, it can be seen that the castings prepared by the cupola smelting process of the present invention have higher strength and toughness. This shows that the cupola smelting process provided by the present invention has a broader market prospect and is more suitable for promotion.
[0085] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0086] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A cupola smelting process, characterized in that: The following steps are involved: S1: Charge pretreatment: Pig iron, scrap steel and recycled materials are selected for charge pretreatment, which are sandblasted, crushed and sieved, and then adsorbent is added to mix; S2: furnace body treatment, using furnace repair materials to evenly coat the inner wall of the furnace body to complete the furnace body treatment; S3: charging process, charging in the order of bottom coke, furnace charge, layer coke and limestone, and completing the charging process; S4: Smelting treatment, burning the bottom coke and the layer coke through oxygen-enriched blast smelting to complete the smelting treatment of the charge; S5: pouring process: the smelted charge is discharged through the iron outlet of the furnace body, and is magnetized and poured into the mold.
2. The cupola smelting process according to claim 1, characterized in that: The charge pretreatment method is as follows: the charge is selected from pig iron, scrap steel and recycled charge, the mass ratio of pig iron, scrap steel and recycled charge is 5:3:2, then quartz sand is sent into a sandblasting machine, the charge is placed within the working range of the sandblasting machine, the pressure of the sandblasting machine is set to 0.6-0.8MPa, the distance between the sandblasting gun and the drill bit is 150-200mm, the sandblasting gun maintains a displacement speed of 0.6-0.8mm, after the sandblasting is completed, the charge is crushed by a jaw crusher, the jaw crusher is set at 200-300r / min for 10-20min, the crushed charge is sieved with a 2-5 mesh screen, and then the sieved charge and adsorbent are added to a mixer for mixing, the mass ratio of the charge box and the adsorbent is 1:0.005, and the pretreatment of the charge is completed.
3. The smelting process of the cupola according to claim 2, characterized in that: The adsorbent is prepared by mixing calcium oxide and magnesium oxide, the mass ratio of calcium oxide to magnesium oxide is 7:3, the purity of the calcium oxide is 95%, and the purity of the magnesium oxide is 92%.
4. The smelting process of the cupola according to claim 1, characterized in that: The repair material in the furnace body treatment in S2 is prepared by the following method: memory alloy powder and carbon fiber are pretreated and then added into a mixer together with silicon carbide powder, aluminate cement and graphite powder for mixing.
5. The cupola smelting process according to claim 4, characterized in that: The particle size of the silicon carbide powder is 20-60 μm, the particle size of the aluminate cement is 30-70 μm, the particle size of the graphite powder is 10-40 μm, and the shape memory alloy powder is nickel-titanium shape memory alloy powder.
6. The cupola smelting process according to claim 5, characterized in that: The memory alloy powder pretreatment method comprises the following steps: after sieving the memory alloy powder with a 200-mesh screen, adding the memory alloy powder into a glass container, and adding a hydrofluoric acid solution for soaking; during the soaking process for 5-10 minutes, continuously stirring with a magnetic stirrer at a stirring speed of 1000-1500 r / min; after the soaking is completed, washing with clean water for 6-8 times, and then drying in a dryer at a drying temperature of 60-80° C. and a drying time of 1-2 hours, thereby completing the pretreatment of the memory alloy powder; the mass ratio of the memory alloy powder to the hydrofluoric acid solution is 1:0.7, and the concentration of the hydrofluoric acid solution is 4%.
7. The cupola smelting process according to claim 6, characterized in that: The carbon fiber pretreatment method is to put the carbon fiber into an ultrasonic cleaning machine, treat it for 16 to 20 minutes under the condition of 160 to 200 kHz, take it out and drain it, so as to complete the pretreatment of the carbon fiber.
8. The cupola smelting process according to claim 1, characterized in that: The charging method is as follows: adding bottom coke at the bottom of the furnace body with a thickness of 10-20 cm, adding furnace charge on the bottom coke with a thickness of 15-25 cm, then adding layer coke with a thickness of 3-5 cm, and finally adding limestone with a thickness of 10-30 mm, and then repeating the above charging sequence to achieve alternating charging. Both the bottom coke and the layer coke are metallurgical coke with a carbon content of 85%, and the charging process is completed.
9. The cupola smelting process according to claim 1, characterized in that: The smelting treatment method is to use a blower to carry out oxygen-enriched blast smelting, the oxygen content is 25%-30%, the blast intensity is 100-200m 3 / (㎡·h), set the melting temperature to 1500-1600℃, the melting time to 20-30min, and complete the melting process.
10. The cupola smelting process according to claim 9, characterized in that: The pouring treatment method is as follows: after the internal furnace charge is smelted, the molten iron is discharged through the furnace body discharge port, and a magnetic field generator is used for magnetization treatment during the discharge process, and the magnetic field strength is 0.05-0.08T, and then poured into a mold, and taken out after cooling to obtain a casting.
Citation Information
Patent Citations
Melting process for cupola furnace
CN105734395A